2017
DOI: 10.1155/2017/4527597
|View full text |Cite
|
Sign up to set email alerts
|

Use of High-Flow Nasal Cannula Oxygen Therapy in a Pregnant Woman with Dermatomyositis-Related Interstitial Pneumonia

Abstract: A 33-year-old pregnant woman was referred to our hospital with respiratory distress at 30 weeks of gestation. Chest computed tomography (CT) scans revealed pulmonary infiltrates along the bronchovascular bundles and ground-glass opacities in both lungs. Despite immediate treatment with steroid pulse therapy for suspected interstitial pneumonia, the patient's condition worsened. Respiratory distress was slightly alleviated after the initiation of high-flow nasal cannula (HFNC) oxygen therapy (40 L/min, FiO2 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Examples of clinical case studies for treating pregnant patients with DM or PM, especially CADM, are relatively rare, and case studies of a similar nature that we were able to identify are shown in supplementary material (18,(26)(27)(28). Tomohiro et al (18). described the case of a 33-year-old pregnant woman who developed progressive interstitial pneumonia (IP) complicated by anti Jo-1 positive ASS at 28 weeks of gestation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Examples of clinical case studies for treating pregnant patients with DM or PM, especially CADM, are relatively rare, and case studies of a similar nature that we were able to identify are shown in supplementary material (18,(26)(27)(28). Tomohiro et al (18). described the case of a 33-year-old pregnant woman who developed progressive interstitial pneumonia (IP) complicated by anti Jo-1 positive ASS at 28 weeks of gestation.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that immunosuppressants should be used early in patients with RP-ILD, since the damage caused to the pulmonary tissue may be irreversible once CADM is complicated by RP-ILD, which may result in the patient being irresponsive to combination immunosuppressive therapy, leading to death after only a few months (17). However, the use of immunosuppressants may not ensure rapid remission of the patient's condition (18). It was reported that combination immunosuppressive therapy consisting of high-dose corticosteroids, cyclosporine and intravenous immunoglobulin might be effective for CADM patients with RP-ILD (16).…”
Section: Discussionmentioning
confidence: 99%
“…4 Only 2 of 68 pregnancies (2.94%) after DM/PM onset were complicated by hypertension 6 . The most frequently mentioned complication of DM/PM was interstitial lung disease 19–23 . The rate of cesarean delivery ranged from 23.3% 6 to 88.2% 5 (Supplementary Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…6 The most frequently mentioned complication of DM/PM was interstitial lung disease. [19][20][21][22][23] The rate of cesarean delivery ranged from 23.3% 6 to 88.2% 5 (Supplementary Tables S1 and S2).…”
Section: Pregnancy In Dm/pmmentioning
confidence: 99%
“…Also, haemodynamic perturbations frequently follow, which may affect the foetus. Though few reports of HFNO use during RA in severe ARDS exist,[ 5 ] it is infrequently used in the OR, although it may be a valuable alternative to intubation.…”
mentioning
confidence: 99%